2018
DOI: 10.1186/s13662-018-1613-z
|View full text |Cite
|
Sign up to set email alerts
|

A fractional order SIR epidemic model with nonlinear incidence rate

Abstract: In this paper, a fractional order SIR epidemic model with nonlinear incidence rate is presented and analyzed. First, we prove the global existence, positivity, and boundedness of solutions. The equilibria are calculated and their stability is investigated. Finally, numerical simulations are presented to illustrate our theoretical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…The functional response of feeding prey by susceptible predator Not long ago, many researchers began to study fractional biological models [1,10,20,25]. In article [14], a dynamic system modelling a prey-predator with harvest area and reserve for prey in the presence of competition and toxicity.…”
Section: Parameters and Variables Explanationmentioning
confidence: 99%
“…The functional response of feeding prey by susceptible predator Not long ago, many researchers began to study fractional biological models [1,10,20,25]. In article [14], a dynamic system modelling a prey-predator with harvest area and reserve for prey in the presence of competition and toxicity.…”
Section: Parameters and Variables Explanationmentioning
confidence: 99%
“…(10) and (12), a new iterative technique can also be considered, which has been framed in the later sections. (13) in which N i is a nonlinear operator.…”
Section: Formulation Of the Modelmentioning
confidence: 99%
“…Hamdan and Kilicman [12] studied the dynamical behaviour of a virus dynamics model with general incidence rate and cure rate for dengue transmission. Mouaouine et al [13] studied the vigorous deportment of a virus dynamics model with broad occurrence rate and cure rate. Wang et al [14] presented the delayed fractional-order SIR (susceptible and removed) epidemic model with saturated incidence and treatment functions.…”
mentioning
confidence: 99%
“…As such, in recent years, fractional calculus has become an intriguing field. Several researchers have shown that models that utilize fractional calculus are more likely to replicate real-world problems compared those that use integer-order differential equations since fractional-order differential equations are able to capture memory effects [20,21].…”
Section: Introductionmentioning
confidence: 99%